Trockij, Simone Weil e i “nobili amici della rivoluzione” - Franco, Alessia (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2023)
This essay aims to reconstruct the controversy between Trockij and the so-called french “democratic communists”, especially Simone Weil, in the early 1930s concerning the nature of the Soviet Union as a workers’ state. To this purpose, the theoretical exchanges and biographical contacts that took place between the two thinkers are collected and analysed, examining in particular their argument in the press on the topics of the October Revolution, the Bolshevik party, the political role of Stalin, bureaucracy in the USSR and the characteristics of the so-called “techno-bureaucratic” society. The latter is considered by Weil as a third form of state, distinct from both the advanced capitalist state and an ideal workers’ state, and identified by her with the Soviet Union under Stalin. Trockij rebuts Weil’s arguments in terms of method and content, attempting to define in Marxist terms what a workers’ state is or should be, and tracing Weil’s critique back to its Kantian matrix. Trockij; Simone Weil; Soviet Union; Revolution; Workers’ State; Marxism.